Psychological responses, mental health, and sense of agency for the dual challenges of climate change and the COVID-19 pandemic in young people in the UK: an online survey study. Issue 9 (September 2022) - Lawrance, Emma L; Jennings, Neil; Kioupi, Vasiliki; Thompson, Rhiannon; Diffey, James; Vercammen, Ans
Summary: Background: The COVID-19 pandemic and climate change are both significant and pressing global challenges, posing threats to public health and wellbeing. Young people are particularly vulnerable to the distress both crises can cause, but understanding of the varied psychological responses to both issues is poor. We aimed to investigate these responses and their links with mental health conditions and feelings of agency. Methods: We conducted an online survey between Aug 5 and Oct 26, 2020, targeting a diverse sample of young people (aged 16–24 years, n=530) in the UK. The survey was distributed using a combination of a survey panel (panel sample) and direct approaches to youth groups and schools who shared the survey with young people in their networks (community sample). We collected data on respondents' psychological responses to both climate change and the COVID-19 pandemic, their sense of agency to respond to each crisis, and the range of impacts on their lives. We also collected demographics data and screened for mental health and wellbeing indicators. We used non-parametric tests for most statistical comparisons. For paired samples, we used Wilcoxon's signed-rank test, and used Mann-Whitney U-tests or Kruskal-Wallis tests for two or more independent samples. Summed scale scores were considered as interval-level data and analysed with Student's t tests and ANOVAs. Effect sizes are reported as Cohen's d and partial eta-squared (η· 2 p ), respectively. Findings: After excluding 18 suspected bots and 94 incomplete responses, 530 responses were retained for analysis. Of the 518 respondents who provided demographic data, 63% were female, 71·4% were White, and the mean family affluence score was 8·22 (SD 2·29). Most participants (n=343; 70%) did not report a history of diagnosis or treatment for a mental health disorder, but mental health scores indicated a common experience of (relatively mild) symptoms of anxiety, depression, and stress. Although UK youth reported more life disruption and concern for their future due to the COVID-19 pandemic, climate change was associated with significantly greater distress overall, particularly for individuals with low levels of generalised anxiety. The COVID-19 pandemic was more associated with feelings of anxiety, isolation, disconnection, and frustration; distress around loss and grief; and effects on quality of life. Climate change was more likely to evoke emotions such as interest and engagement, guilt, shame, anger, and disgust. The greater distress attributed to climate change overall was due, in particular, to higher levels of guilt, sense of personal responsibility, and greater distress triggered by upsetting media coverage. Agency to address climate change was associated with greater climate distress, but pandemic-related distress and agency were unrelated. Interpretation: The COVID-19 pandemic and climate change are affecting the wellbeing of UK young people in distinct ways, with implications for health service, policy, and research responses. There is a need for mental health practitioners, policy makers, and other societal actors to account for the complex relationship between climate agency, distress, and mental wellbeing in young people. Funding: Imperial College London.